Spiritual care als toekomst van de geestelijke verzorging - Carlo Leget (Religie & Samenleving)
Since some time chaplaincy as a discipline is in a crisis of both legitimization and communication. In this contribution, which is limited to the health care sector, a possible way out of this double crisis is sketched by joining an international field of studies which is known as spiritual care. Here a central idea is that attention to meaning and spirituality is the task of every care giver. According to this interdisciplinary approach the chaplain has a special role. On the basis of the first Dutch guideline spiritual care, written for physicians and nurses, a plea is made for a further development of chaplaincy as a discipline by embedding it into the spiritual care approach.